Digestion of micellar casein in duodenum cannulated pigs. Correlation between in vitro simulated gastric digestion and in vivo data. (1st May 2021) - Miralles, B.; Sanchón, J.; Sánchez-Rivera, L.; Martínez-Maqueda, D.; Le Gouar, Y.; Dupont, D.; Amigo, L.; Recio, I.
Highlights: Similar peptide profile between duodenum and simulated gastric phase. Homogeneity of the outflowed material from the stomach at different time points. The pig duodenal content showed fluctuating amounts of intact caseins. In vivo and in vitro free amino acids show comparable profiles. Abstract: Correlation and validation of the results of simulated gastrointestinal digestion of food compounds towards in vivo data is essential. The objective of this work was to monitor the digestion of milk micellar casein in the porcine upper intestinal tract and to match the outcome with the gastric in vitro digestion following the Infogest harmonized protocol. In pig duodenum, small amounts of intact caseins were present in all samples, while caseins were observed up to 60 min of gastric in vitro digestion. The peptide profile generated after in vitro and in vivo digestion showed clear similarities with specific overrepresented regions rich in proline and other hydrophobic residues. The statistical comparison of the in vivo and in vitro peptidome resulted in satisfactory correlation coefficients, up to 0.8. Therefore, the in vitro protocol used was a robust and simple model that provides a similar peptide profile than that found in porcine duodenum.